Experiences Designing and Building a Multi-Hop Wireless Ad Hoc Network Testbed - Maltz, Dave; Broch, Josh; Johnson, David B. (1999)
In this paper, we describe our experiences building a multi-hop wireless ad hoc network of 8 nodes driving around a 700 m by 300 m site. Each node runs the Dynamic Source Routing (DSR) protocol and interfaces seamlessly with existing Internet infrastructure and the Mobile IP protocol. The issues discussed in this paper range from logistical and management issues, to protocol design and performance analysis issues. We also present an early characterization of the testbed performance, and describe a significant new challenge for ad hoc network routing protocols. The major goal of the paper, however, is to share our experiences, in the belief that they may be useful to others who attempt to build other ad hoc network testbeds.
CMU School of Computer Science Technical Report